SOIL DRIVE NUTRIENT AS NEW METHOD FOR TIN MINING REMEDIATION - Anton Muhibuddin (Journal of Environmental Engineering and Sustainable Technology, 2018)
A contaminated soil by tin usually is a big problem in Indonesia. Uniformity is essential for processing soil at a normal quality and to ensure conformity to specify clean up levels. Revegetation efforts were carried out by using rubber and jatropha combination which infected by arbuscular mycorrhizal (VAM) fungi applied using the soil drive nutrient (SDN) method showed good result in the previously research.This research purposes to know the effectivity of soil drive nutrient (SDN) method to promote the growth of soybean plants (Glysine max L.) in tin mining soil. The results showed that the cropping pattern and dose of mycorrhizal gave effect on soybean growth, especially on the trunk diameter. Result also showed that mycorrhizal infection on soybean roots significantly influenced by the SDN method and dose of mycorrhizal that applied. Both of these are expected to have a positive impact on soybean production and resistance to environmental stress and disease attack. Viceversa, height and number of plant leaves untill 28 days were not affected by the SDN method and the dose of mycorrhiza applied.